The Role of Islamic Financial Literacy in Moderating the Relationship between QRIS and Financial Inclusion - Abdillah Dwi Prasetyo; Muhammad Khoirul Fikri; Shaherbano Ijaz (IAIN Syekh Nurjati Cirebon, 2026)
This study investigates the relationship between the effectiveness and efficiency of the Quick Response Code Indonesian Standard (QRIS) and financial inclusion, with Islamic financial literacy serving as a moderating variable. Employing a quantitative approach, data were collected from university students and analyzed using moderated regression analysis to evaluate both direct and interaction effects. The findings indicated that QRIS effectiveness and efficiency exert a positive and significant influence on financial inclusion. Furthermore, Islamic financial literacy enhances the relationship between QRIS utilization and financial inclusion, suggesting that higher literacy levels amplify the inclusive benefits of integrating digital payment systems within an Islamic financial framework. These results highlight the importance of integrating digital payment innovation with Islamic financial literacy programs to promote inclusive and sustainable financial ecosystems. Additionally, Islamic financial literacy moderates the relationship between QRIS effectiveness and financial inclusion, but does not influence the association between QRIS efficiency and financial inclusion. Overall, students' understanding of Islamic finance strengthens the impact of QRIS effectiveness in promoting financial inclusion.